Structural characteristics of Cu/Ti bimetal composite produced by accumulative roll-bonding (ARB) - Hosseini, M.; Pardis, N.; Manesh, H. Danesh; Abbasi, Majid; Kim, Dong-Ik (Elsevier BV, 2017)
Cu/Ti nanostructured bimetal composite was produced by accumulative roll-bonding (ARB) technique and the structural characteristics of this composite were studied both experimentally and by finite element analysis. Macrostructure evolution of the composite layers was investigated by optical and scanning electron microscopes. In addition, transmission electron microscopy (TEM) as well as energy-dispersive X-ray spectroscopy (EDX) techniques were utilized for detailed microstructural investigations. Different finite element simulations were designed based on the experimental results. The results were combined with macrostructural observations to gain a better insight into the fragmentation mechanismof the Ti reinforcements. Necking of the Ti layers was observed after 3 cycles of ARB processing which was found to happen at shear bands, after sufficient work-hardening of the constituents. Further processing resulted in fragmentation and distribution of lens shaped Ti constituents. It was found that such a shape evolution makes it more difficult to deform the Ti segments by further straining and consequently, a more localized strain concentration happens within the Cu matrix near these segments. A significant grain refinement was observed by TEM investigation of the highly strained composite. ARB processing of Cu/ Ti bimetal composite resulted in nanostructured Ti reinforcements distributed within an ultrafine-grained Cu matrix. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: SEVERE PLASTIC-DEFORMATION; STACKING-FAULT ENERGY; HIGH-PRESSURE TORSION; GRAIN-SIZE; MECHANICAL-PROPERTIES; BULK MATERIALS; SHEAR BANDS; MICROSTRUCTURE; TEMPERATURE; EVOLUTION